Marketplaces as the basis of e-commerce: technological potential and investment horizons - S.V. Pokhylko; Y.S. Shvydka (Економіка, управління та адміністрування)
The article highlights the theoretical aspects of e-commerce as the foundation of the modern economy. The study examines the main trends in the industry’s development and emphasizes its rapid growth worldwide. It analyzes the theoretical foundations of marketplaces and their role in the platform economy. An important component of the study is the analysis of the dynamics of the total value of goods sold on marketplaces and the examination of the largest marketplaces by gross profit.